2014
DOI: 10.3791/50882
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Analysis of Cortisol from Human and Monkey Hair

Abstract: The stress hormone cortisol (CORT) is slowly incorporated into the growing hair shaft of humans, nonhuman primates, and other mammals. We developed and validated a method for CORT extraction and analysis from rhesus monkey hair and subsequently adapted this method for use with human scalp hair. In contrast to CORT "point samples" obtained from plasma or saliva, hair CORT provides an integrated measure of hypothalamic-pituitary-adrenocortical (HPA) system activity, and thus physiological stress, during the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 18 publications
3
151
0
Order By: Relevance
“…Samples were stored in a foil pouch at −80°C until shipment to the Hormone Assay Core Laboratory at the University of Massachusetts Amherst. Following Meyer et al (2014), samples were weighed, washed twice with isopropanol and dried for 5–7 days under a fume hood. For all hair assays, we used the entire length of the shaved hair, as the founding study validating the hair cortisol assay in rhesus macaques found no significant difference in proximal versus distal hair segments when hair samples were divided in half (Davenport et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were stored in a foil pouch at −80°C until shipment to the Hormone Assay Core Laboratory at the University of Massachusetts Amherst. Following Meyer et al (2014), samples were weighed, washed twice with isopropanol and dried for 5–7 days under a fume hood. For all hair assays, we used the entire length of the shaved hair, as the founding study validating the hair cortisol assay in rhesus macaques found no significant difference in proximal versus distal hair segments when hair samples were divided in half (Davenport et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Diurnal variations are not applicable to this procedure, and cortisol levels are very stable in hair samples (226). On the other hand, there are some drawbacks; for example, the effects of short-lived stressors are difficult to detect using this technique.…”
Section: Indicators Of Hpa Axis Activitymentioning
confidence: 99%
“…It was suggested that structural damage of distal hair segments might have been caused by liquids like water and cosmetics (Kirschbaum et al 2009), or alcohol used to wash the samples before analysis (Manenschijn et al 2011). In monkey hair, the amount of cortisol remaining after washing was inversely related to the number of shampoo exposures (Meyer et al 2014). Assuming that hair in humans grows approximately 1 cm per month and that humans typically wash their hair at least several times per week, hair located several centimetres from the scalp might be exposed to over-shampooing, which appears to be a significant contributor to variation in cortisol levels (Meyer et al 2014).…”
Section: Washing-out Effectmentioning
confidence: 99%
“…In monkey hair, the amount of cortisol remaining after washing was inversely related to the number of shampoo exposures (Meyer et al 2014). Assuming that hair in humans grows approximately 1 cm per month and that humans typically wash their hair at least several times per week, hair located several centimetres from the scalp might be exposed to over-shampooing, which appears to be a significant contributor to variation in cortisol levels (Meyer et al 2014). Stalder and Kirschbaum (2012) suggested that frequent washing procedures may partially influence HCC in humans but it is unknown whether dogs are similarly affected.…”
Section: Washing-out Effectmentioning
confidence: 99%